A REVIEW OF THE INTEGRATION OF TRADITIONAL AND MODERN MEDICINE - Ntombizanele Tshali,; Karishma Singh ,; Afika-Amazizi Naledi Mbuyiswa ,; Portia Nokubonga Mseleku , (Student's Journal of Health Research Africa, 2024)
The integration of traditional medicinal plant knowledge with contemporary pharmaceutical research has enormous potential for the development of novel and cutting-edge modern medication. This study explores how indigenous and traditional uses of medicinal plants can informatively enhance drug discovery and development procedures. Traditional knowledge, honed over decades, frequently includes a thorough understanding of plant-based cures and their therapeutic applications. Case studies where traditional medicinal plants have been used to formulate new drugs will be examined. For instance, the discovery of artemisinin from the traditional Chinese medication sweet wormwood has revolutionized the treatment of malaria. The Madagascar periwinkle, which was traditionally used to treat diabetes, is now the source of the pediatric cancer treatments vinblastine and vincristine. Technologies and methods that can be used to accelerate the translation of traditional practices into modern medicine will also be evaluated. These include systems biology techniques, metabolomics, and high-throughput screening to clarify the mechanisms of action of traditional treatments. Through the documentation of the safety, efficacy, and chemical composition of traditional remedies, researchers can confirm their effectiveness and possibly identify active ingredients for additional research. This approach makes use of indigenous knowledge of traditional medicine to treat modern health issues while also acknowledging the cultural and historical relevance of the practice. Additionally, opportunities and challenges in this multidisciplinary collaboration will be identified.